Transmissibility performance assessment for drive-by bridge inspection. (1st September 2021) - Makki Alamdari, M.; Chang, K.C.; Kim, C.W.; Kildashti, K.; Kalhori, H.
Highlights: The feasibility assessment of drive-by bridge inspection is investigated. A novel index to quantify the transmissibility performance is proposed. An induced change is identified through drive-by bridge inspection. Successful identification of the first three modes of the bridge is verified. Abstract: This paper presents results of numerical and experimental investigations for the feasibility assessment of drive-by bridge inspection, where the health status of a bridge is solely identified from the dynamic response of an inspection vehicle, passing over a target bridge. To this aim, a novel metric based on the transmission performance between the vehicle and the bridge is proposed, and it is demonstrated that the vehicle having a higher sensitivity index has superior performance, in moving state, to identify bridge frequencies, and consequently separate different states of a bridge from one another. In addition to numerical validation, experimental validation from a laboratory-based experiment is presented, where a two-axle vehicle model is adopted as an inspection vehicle and a single-span steel beam is employed as a target bridge. Vibration data are collected using three highly sensitive accelerometer sensors installed on the vehicle, one at the middle of each axle, i.e., the front axle, and the rear axle, and the third one at the center of gravity of the vehicle, to measure the pitching and bouncing modes of the vehicle. The contributions and the key findings of the work are as follows: First, this paper presents one of the early attempts of experimentally validating the feasibility of drive-by bridge inspection to identify an induced change in the structure of a bridge which has caused less than 2% variation in the fundamental frequency. Second, a novel index for quantifying the performance of transmission between the bridge and the vehicle is proposed. It is verified that a vehicle with a higher sensitivity index captures more bridge-related information, hence making the bridge modal frequencies more identifiable. Third, through experiments, successful identification of the first three vibration modes of the bridge, obtained from the moving vehicle tests, is verified under the condition of constant and slow speed, when there is ongoing excitation on the bridge. Fourth, the indices and criteria presented herein would be helpful in designing a real drive-by inspection system which can be potentially used for drive-by bridge inspection of a network of bridges with similar structural design in practice.